2019
DOI: 10.1016/j.neuroimage.2019.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Word inversion sensitivity as a marker of visual word form area lateralization: An application of a novel multivariate measure of laterality

Abstract: An area within the ventral occipitotemporal cortex (vOTC), the "visual word form area" (VWFA), typically exhibits a strongly left-lateralized response to orthographic stimuli in skilled readers. While individual variation in VWFA lateralization has been observed, the behavioral significance of laterality differences remains unclear. Here, we test the hypothesis that differences in VWFA lateralization reflect differing preferences for holistic orthographic analysis. To examine this hypothesis, we implemented a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 67 publications
4
26
0
Order By: Relevance
“…Previous studies showed that when subjects process words that refer to common concrete objects, the implied average size or sound are individually separately represented in visual and auditory areas, respectively (e.g., Borghesani et al, 2016;Borghesani et al, 2019;Coutanche 2019;Kiefer et al, 2008). These results are in line with a recent proposal (Borghesani and Piazza, 2017) that suggests that semantic representations of concrete words can be conceived as points in multidimensional spaces where different dimensions represent the different characteristics that define the meaning of a word.…”
Section: Sensory Regions Represent Distances Travelled Along Separatesupporting
confidence: 80%
See 1 more Smart Citation
“…Previous studies showed that when subjects process words that refer to common concrete objects, the implied average size or sound are individually separately represented in visual and auditory areas, respectively (e.g., Borghesani et al, 2016;Borghesani et al, 2019;Coutanche 2019;Kiefer et al, 2008). These results are in line with a recent proposal (Borghesani and Piazza, 2017) that suggests that semantic representations of concrete words can be conceived as points in multidimensional spaces where different dimensions represent the different characteristics that define the meaning of a word.…”
Section: Sensory Regions Represent Distances Travelled Along Separatesupporting
confidence: 80%
“…In a recent proposal (Borghesani and Piazza, 2017), starting from the assumption that semantic representations of concrete words (e.g., "tomato") are points in multidimensional spaces where each dimension represents specific characteristics of the object referred to by the word (e.g., red color, roundish shape, small size), we suggested that the different dimensions are coded both conjunctively (in convergence zones, and here demonstrated through spatialcodes), but also separately, in the same brain regions that respond to those features when the objects are physically presented. In support of the idea we and others found that when subjects process words that refer to concrete objects the implied average size or sound associated are indeed separately represented in visual or auditory areas, respectively (e.g., Borghesani et al, 2016;Borghesani et al, 2019;Coutanche 2019;Kiefer et al, 2008). Here we looked at the whole brain level to reveal whether and where separate representational maps of size and pitch existed.…”
supporting
confidence: 83%
“…In contrast, individuals with right-lateralization of language areas have a higher probability of an atypical VWFA right-lateralization and FFA left-lateralization in course of development ( Gerrits et al, 2019 ). Furthermore, recent literature revealed that the VWFA is mostly left-lateralized in readers of alphabetic writing systems (e.g., English and German), while readers of non-alphabetic writing systems (e.g., Chinese) often exhibit bilateral engagement of the left and right VWFA ( Carlos et al, 2019 ). Alphabetic orthographies may bias readers toward analytic visual strategies, whereas non-alphabetic orthographies may bias readers toward holistic visual strategies that emphasize the overall structure of a word.…”
Section: Introductionmentioning
confidence: 99%
“…This analytic strategy would suggest a stronger recruitment of the left hemisphere during face processing in children compared to adults ( Meng et al, 2012 ). The use of a holistic versus analytic strategy and therefore right- or left-lateralization of FFA and VWFA might further be driven by different reading instruction methods in early readers ( Carlos et al, 2019 ). However, as only right-handed subjects of the alphabetic writing system (i.e., German) were included in the present study, a typical left-lateralization of the VWFA was expected.…”
Section: Introductionmentioning
confidence: 99%
“…The differential mode of processing often attributed to the two hemispheres-the right hemisphere excels at holistic processing of information whereas the left excels at analytic [10]-and the typical perceptual and cognitive development going from the holistic toward the analytic mode [11] (but see also [12]), support this theory. Furthermore, the recent finding that adults who are the most sensitive to inversion of the words (rotation of 180 • and right-to-left writing) are those who engage the right visual word form area the most [13], reinforces the possible role of the two cerebral hemispheres in the differential use of the two modes of processing. Importantly, this first sort of theoretical account leads to mainly attributing the problem of mirror reversal confusion to some persons or populations.…”
Section: Introductionmentioning
confidence: 75%